PENGARUH KONSENTRASI DAN INTERVAL WAKTU PENYEMPROTAN BIOPESTISIDA BABANDOTAN TERHADAP INTENSITAS KERUSAKAN DAN HASIL TANAMAN KAILAN - Oktaviana Limbong; Budi Adi Kristanto; Florentina Kusmiyati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[EFFECT OF CONCENTRATION AND TIME INTERVAL OF BABANDOTAN BIOPESTICIDE SPRAYING ON THE INTENSITY OF DAMAGE AND YIELD OF KAILAN]. Biopesticides from Ageratum conyzoides plants are used as an alternative in pest control. The used of synthetic pesticides was widespread as an effort in pest and disease control because it worked effectively and quickly, but caused resistance and resurgence of pests were bad impact on the environment for long term. The content of active compounds in Ageratum conyzoides plants such as flavonoids, anthraquinone, tannins, terpenes, phenols, saponins, alkaloids and steroids worked as controllers of various cultivated plant pests. This study aims to determine the spraying concentration and interval of spraying Ageratum conyzoides on the intensity of damage and yield of kailan plants. This research was conducted in November 2020 - January 2021 at Agroecotechnopark research land, Diponegoro University, Semarang. The experimental design used was a factorial Randomized Complete Block Design with 3 replications. The first factor was spraying concentration (10%, 30% and 50%) and the second factor was interval of spraying (once every 5 days, 10 days and 15 days). The variables observed were absolute damage rate, relative damage rate, plant height, number of leaves and fresh weight of kailan. Data were analyzed by Analysis of Variance followed by DMRT (Duncan's Multiple Range Test). The results showed that Ageratum conyzoides biopesticide was able to control pests and and to support kailan growth. Spraying babandotan biopesticide at a concentration of 50% has been able to reduce the rate of crop damage by pests, supported vegetative growth, and increased kailan growth to provide optimal yield. Spraying time interval did not affect all variables.